The Position of Women as the Second Sex in "The Kreutzer Sonata" by Leo Tolstoy - Tuti Andriani; Murni Mahmud; Muftihaturrahmah Burhamzah (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
This research aimed at analyzing the position of women as the second sex in the novel â€œThe Kreutzer Sonataâ€ written by Leo Tolstoy. The writer used descriptive qualitative method and the theory of gender feminism. This research analyzed about feminism but focused on the position of women according to the inequalities of gender; marginalization, subordination, stereotype, violence, and double workloads. The results of this research showed that the position of women in the novel based on the inequalities of gender is the second sex. This novel shows that women as the second sex in patriarchal culture have certain limits in doing things in their lives. The position of women under men where men were considered as the main sex which has an important role in society.